Educator Resource Management at Nurul Falah IT High School Bandar Lampung - Yuniar, Yuniar (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research uses a qualitative approach, data analysis using the Miles Huberman and Saldana interactive model with steps: 1). Data collection, 2). Data condensation, 3). Presentation of data, and 4). Drawing conclusions. For data validity using Triangulation and Member check. There are 2 triangulations used, namely, source triangulation and method triangulation. Findings: 1). Planning of teaching resources999: at the beginning of each school year the school makes a plan of activities and school budgets in which there are activities regarding the needs and development of teaching resources and planning for recruitment, first analyzing the mapping of lesson hours so that the needs of teaching staff are known. 2). Recruitment and Selection at SMA IT Nurul Falah Bandar Lampung: a). recruitment patterns applied internally. b) selection carried out includes administrative selection and interviews. 3). Development and Training at SMA IT Nurul Falah Bandar Lampung: To improve and develop the potential of educators (teachers), the school conducts training such as In House Training (IHT), besides that the school also provides opportunities for educators (teachers) to further improve and develop their potential by participating in activities / workshops outside the school in the hope that it can have a positive effect on the progress of the school.